MANAJEMEN PEMBERDAYAAN MASYARAKAT BERBASIS MASJID DI KOTA PONTIANAK - Cucu Cucu; Santa Rusmalita (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2019)
The function of sosilal masjidcan be played precisely when modern management principles are applied in the management of masjid. The function of the masjid is not only a function of worship, but also a masjid can be used as a media for empowering da'wah. Da'wah empowerment of the community is a missionary movement that is a real action carried out professionally in a da'wah institution by implementing modern management functions, in order to bring about change, namely the improvement of religious quality and social quality. Community empowerment is motivated by various weaknesses in the community. Through zakat and infaq funds, masjid administrators can manage it as a source of community empowerment. Through field interviews found at the Daarul Falah Masjid in Pontianak City, there is a community empowerment program that has two objectives, namely increasing mosque funding and improving the quality of the community. The types of empowerment intended consisted of: Business capital assistance, basic food subsidy assistance, scholarship assistance, medical assistance, kiosk rental, multipurpose building rentals. In its management Daarul Falah Masjid has implemented modern management principles, namely: planning, internal and external coordination, formal and non-formal direction, and evaluation. Keywords: Management, Community Empowerment and Masjid Fungsi sosilal masjid dapat diperankan dengan tepat dikala prinsip-prinsip manajemen modern diterapkan dalam pengelolaan masjid. Fungsi masjid bukan hanya fungsi ibadah mahdlah, tetapi juga masjid dapat difungsikan sebagai media dakwah pemberdayaan. Dakwah pemberdayaan masyarakar merupakan gerakan dakwah yang bersifat tindakan nyata yang dilakukan secara professional dalam sebuah lembaga dakwah dengan menerapkan fungsi-fungsi manajemen modern, guna mewujudkan perubahan yakni peningkatan kualitas keagamaan dan kualitas sosial. Pemberdayaan masyarakat dilatarbelakangi adanya berbagai kelemahan pada masyarakat. Melalui dana zakat dan infak umat, pengurus masjid dapat mengelolanya menjadi sumber pemberdayaan masyarakat. Melalui wawancara lapangan ditemukan di Masjid Daarul Falah Kota Pontianak terdapat program pemberdayaan masyarakat yangmemiliki dua sasaran, yaitu peningkatan dana masjid dan peningkatan kualitas masyarakat. Jenis pemberdayaan dimaksud terdiri dari : Bantuan modal usaha, bantuan subsidi sembako, bantuan beasiswa, bantuan pengobatan, penyewaan kios, penyewaan gedung serbaguna. Dalam pengelolaannya Masjid Daarul Falah telah menerapkan prinsi-prinsip manajemen modern yaitu: perencanaan, koordinasi intern dan ekstern, pengarahan formal dan non formal, dan evaluasi. Kata Kunci: Manajemen, Pemberdayaan masyarakat dan Masjid